Role of Market Intelligence in Improving Livelihood of Rural Farmers in Meghalaya - Roy, A.; Tripathi, A. K.; Singh, N. U.; Dkhar, D. S. (Indian Journal of Hill Farming, 2018)
Agriculture is the main stay of the people in Meghalaya in which about 80 % of the total population still depends for their livelihood. However, the contribution of this sector to the State's NSDP is only about one-third. The total geographical area of Meghalaya is 22, 429, 00 00 ha, approximately, out of which the net cropped area is 3,39,725 ha of the geographical area. The unutilized potential area is about 5,55,039 ha of the total area under uncultivated lands and the forest cover is 9,46,127 ha. Market intelligence gives insights regarding what might happen in the near future in the market scenario. Pertaining to the state of Meghalaya there are no studies that have been done with regards to market intelligence. Moreover, although Meghalaya has a State Agricultural Marketing board which develops marketing infrastructural facilities and provides marketing support to the farmers in the State. However, it does not look into the matter of price forecasting and advisory. Hence, the present study was attempted to analyze the impact of market intelligence on the rural farmers of Meghalaya. To study the impact of Market Intelligence in Meghalaya, data were collected from five villages viz. Nongthymmai, Nongrim Nongladew, Mawtneng, Mawbri and Mawphrew in Ri-Bhoi District of Meghalaya for five selected crops i.e. potato, tomato, ginger, turmeric and pineapple respectively. Data were collected from two categories of farmers i.e. who received price information for five selected crops and also from those who do not receive price information. The results from the study indicated that the farmers who received market information advisory have received increase in gross returns and net returns for their various crop produce than the previous years. The highest increased in gross returns was seen in ginger which had increased by 5.1% and in net returns it had increased by 4% which was followed by turmeric which had increased by 4% in gross returns and had increased by 3.5 % in net returns. This is because they have adjusted their sowing as well as harvesting time of their crops according to the price advisory information that they have received. The farmers were also able to store their produce for a certain period of time till their product fetches a higher price in the market. Thus we can say that Market Intelligence has benefitted those farmers who have adopted it and has improved their livelihood due to their increased returns from production.